2014
DOI: 10.1017/s0007114514002554
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin lowers plasma TAG concentrations and increases hepatic antioxidant gene expression in diet-induced obesity mice

Abstract: Non-alcoholic fatty liver disease (NAFLD) is significantly associated with hyperlipidaemia and oxidative stress. We have previously reported that astaxanthin (ASTX), a xanthophyll carotenoid, lowers plasma total cholesterol and TAG concentrations in apoE knockout mice. To investigate whether ASTX supplementation can prevent the development of NAFLD in obesity, male C57BL/6J mice (n 8 per group) were fed a high-fat diet (35 %, w/w) supplemented with 0, 0·003, 0·01 or 0·03 % of ASTX (w/w) for 12 weeks. The 0·03 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 44 publications
2
68
0
Order By: Relevance
“…This pigment is responsible for the characteristic pink and red color of seafood such as salmon, trout, shrimp, lobster, and fish eggs [37]. Due to its long chain with conjugated double bonds and keto (C=O) moieties on each ionone ring, astaxanthin is a potent antioxidant that scavenges mostly peroxyl radicals, protecting fatty acids and biological membranes against lipid peroxidation [37,38,39]. For this reason, the potential of this carotenoid in ameliorating oxidative stress-induced diseases such as NAFLD has been studied [36].…”
Section: Astaxanthinmentioning
confidence: 99%
See 2 more Smart Citations
“…This pigment is responsible for the characteristic pink and red color of seafood such as salmon, trout, shrimp, lobster, and fish eggs [37]. Due to its long chain with conjugated double bonds and keto (C=O) moieties on each ionone ring, astaxanthin is a potent antioxidant that scavenges mostly peroxyl radicals, protecting fatty acids and biological membranes against lipid peroxidation [37,38,39]. For this reason, the potential of this carotenoid in ameliorating oxidative stress-induced diseases such as NAFLD has been studied [36].…”
Section: Astaxanthinmentioning
confidence: 99%
“…The results showed that incubation with astaxanthin, but not α-tocopherol, resulted in a dose-dependent decrease in TG accumulation in primary hepatocytes. The mechanism by which astaxanthin decreased lipid accumulation in hepatocytes is suggested to be a reduction in fatty acid uptake as shown by a dose-dependent decrease in expression of cluster of differentiation 36 (CD36) with astaxanthin [38]. …”
Section: Astaxanthinmentioning
confidence: 99%
See 1 more Smart Citation
“…Astaxanthin also inhibits the conversion of xanthine dehydrogenase to xanthine oxidase and the protein carbonyl level in rat liver tissues following ischemia-reperfusion injury (a severe oxidative condition) [16]. Astaxanthin has also been shown to induce expression of nuclear factor-erythroid 2-related factor 2 mRNA and its downstream antioxidant-related genes in the mouse liver [17]. …”
Section: Potential Mechanisms Of Astaxanthin For Liver Protectionmentioning
confidence: 99%
“…However, it is crucial to note that there is a paucity of “human studies” to investigate the effects of astaxanthin treatment on liver function in the clinical setting. Two animal studies have investigated the level of ALT, a clinically well-used marker specific to liver function, was examined under astaxanthin treatment [16, 17]; one study showed that astaxanthin significantly reduced blood ALT levels in mice [17], but in another study, astaxanthin did not change the ALT levels in rats following ischemia-reperfusion injury [16]. Before astaxanthin is confirmed as protective to liver, accumulation of data from such human studies is needed.…”
Section: Potential Mechanisms Of Astaxanthin For Liver Protectionmentioning
confidence: 99%